X‐ray tomography analysis of soil biopores structure under wetting and drying cycles. (21st April 2021) - Cheik, Sougueh; Jouquet, Pascal; Maeght, Jean‐Luc; Capowiez, Yvan; Tran, T.M.; Bottinelli, Nicolas
Abstract: Soil macroporosity is a highly dynamic feature driven by numerous physical and biological processes, of which bioturbation, the movement of water in soil and swelling and shrinking cycles are the main processes. To date, the interaction between these factors, especially how galleries produced by soil fauna respond to rainwater percolation and wetting–drying (WD) cycles, remains poorly known. A laboratory experiment was carried out to expose soil macrofauna galleries to three different consecutive water flow (simulated rain events of 50, 80 and 110 mm h −1 in 1 h) and drying cycles in a clayey soil. X‐ray computed tomography and image analyses were used prior to and after each exposure to assess the water stabilities of galleries and created cracks. The 3D properties (volume, diameter, specific surface area and density) of the galleries produced by termites or ants were not statistically influenced by rainwater percolation and WD cycles, suggesting a high water stability and life expectancy under natural conditions. Conversely, the crack water stability was variable and was probably influenced by the presence of galleries in the same area. This study emphasizes that the macropores created by soil fauna may persist in clayey soil and that there is a need to better understand how cracks and galleries interact. Highlights: Evolution of soil porosity was studied by X‐ray computed tomography. Galleries made by soil fauna were stable and resist to wetting and drying cycles. Cracks were highly variable and were highly influenced by wetting and drying cycles. No relationship could be evidenced between galleries and cracks.